Penguatan Karakter Islami pada Anak Usia Dini dengan Media Permainan Tradisional yang Disesuaikan dengan Nilai Nilai Islam - Ade Ismail Fahmi; Hasanah; Siti Aliyah; Nur Aini Zaida; Naila Attamimi (Bulletin of Community Engagement, 2024)
Traditional games are an important part of local culture that can be used as a learning medium to strengthen Islamic character in early childhood. This community service activity aims to integrate Islamic values ​​into traditional games to support character formation in RA Cahaya Iman students. The method used is the Asset-Based Community Development (ABCD) approach, which actively involves the community in planning, implementing and evaluating the program. The subjects of this activity include teachers, parents and students of RA Cahaya Iman, with intensive training and assistance related to traditional Islamic game-based learning media. The results of the activity show that this approach has succeeded in increasing children's understanding of the values ​​of honesty, responsibility and discipline through game media such as "Congklak" and "Engklek Islami". Teachers and parents are also increasingly actively collaborating in supporting children's learning at school and at home. The implication of this activity is the emergence of social change in the community, including the formation of collective awareness of the importance of Islamic character education and the emergence of new institutions, such as the role of teachers as innovative facilitators. The conclusion of this activity emphasizes the importance of utilizing local assets to create relevant and sustainable educational programs. This program not only strengthens Islamic character education but also builds positive social transformation in the RA Cahaya Iman community